Perspektif Alumni Tentang Pengaruh Kualitas Pelayanan STIPAP-Medan Terhadap Loyalitas Alumni Dengan Kepuasan Sebagai Variabel Intervening (Studi Kasus di STIPAP (Sekolah Tinggi Ilmu Agribisnis Perkebunan) -Medan - Karen Tambunan; Paham Ginting; Prihatin Lumbanraja (CERED Indonesia Institute, 2020)
Education is a process of learning which involves campus actively in developing the students’ potency in having religious spiritual power, self-control, personality, intelligence, morality, and skill needed by them and society. Therefore, each higher education needs to recognize its service quality to the students by using the five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The research used descriptive explanatory method. The data were gathered by using questionnaires. The population was 1,298 alumni of the Department of BDP (Plantation Crop Culture) of STIPA, Medan, and 93 of them were used as the samples. The data were analyzed by using SPSS 22 software program. The result of the research showed that responsiveness had direct, positive, and significant influence on alumni’s satisfaction, assurance had direct, positive, and significant influence on alumni’s satisfaction, and empathy had direct, positive, and significant influence on alumni’s satisfaction at STIPAP, Medan. Tangibles, reliability, responsiveness, assurance, empathy, and alumni’s satisfaction simultaneously had positive and significant influence on alumni’s satisfaction at STIPAP, Medan. Tangibles had direct, positive, and significant influence on alumni’s loyalty, alumni’s satisfaction had direct, positive, and significant influence on alumni’s loyalty, responsiveness had indirect, positive, and significant influence on alumni’s loyalty through alumni’s satisfaction as intervening variable, assurance had indirect, positive, and significant influence on alumni’s loyalty through alumni’s satisfaction as intervening variable,, and empathy had indirect, positive, and significant influence on alumni’s loyalty through alumni’s satisfaction as intervening variable at STIPAP, Medan.